Strengthening of Existing Episodic Memories Through Non-invasive Stimulation of Prefrontal Cortex in Older Adults with Subjective Memory Complaints - Manenti, Rosa; Sandrini, Marco; Gobbi, Elena; Cobelli, Chiara; Brambilla, Michela; Binetti, Giuliano; Cotelli, Maria (Frontiers in Aging Neuroscience, 2017)
Episodic memory is critical to daily life functioning. This type of declarative memory declines with age and is the earliest cognitive function to be compromised in Alzheimer’s disease (AD). Subjective memory complaints (SMC) are commonly reported by older adults and have been considered a risk factor for developing AD. The possibilities for prevention of memory disorders in older adults have increased substantially in recent years. Previous studies have shown that anodal transcranial Direct Current Stimulation (tDCS) applied over the left lateral prefrontal cortex (PFC) after a contextual reminder strengthened existing verbal episodic memories, conceivably through reconsolidation, in elderly people. In this study, we hypothesized that anodal tDCS applied over the left lateral PFC after a contextual reminder would improve delayed memory retrieval relative to placebo (sham) stimulation in elderly individuals with subjective memory complaints. Twenty-two subjects learned a list of words. 24h later, tDCS (anodal or placebo) was applied over the left lateral PFC after a contextual reminder. Memory retrieval was tested 48h and 30 days later. These findings showed that anodal tDCS over the left lateral PFC strengthened existing episodic memories, a behavioral effect documented by improved recognition up to 30 days, relative to placebo stimulation. This study suggests that tDCS after a contextual reminder can induce long-lasting beneficial effects by facilitating the consolidation processes and opens up the possibility to design specific noninvasive interventions aimed at preventing memory decline in this at-risk population.